Weaponized Interdependence Revisited: Trade, Sanctions, and Geoeconomic Power in World Politics - Tri Adianto (Pen of Global Politics, 2026)
Globalization has deepened economic interdependence across trade, finance, and regulatory networks, but this interconnectedness has also created new opportunities for coercion and strategic control. In recent years, sanctions, export restrictions, and network-based economic pressure have become increasingly central to the practice of power in world politics. This article examines how weaponized interdependence helps explain the relationship between trade, sanctions, and geoeconomic power in the contemporary international system. The study employs a qualitative research design grounded in document analysis and guided by the analytical framework of weaponized interdependence and geoeconomic power. Data are drawn from sanctions regulations, trade policy documents, official government statements, institutional reports, and scholarly works addressing network asymmetry, economic coercion, and strategic interdependence. The analysis focuses on key dimensions including network centrality, chokepoint control, dependency relations, institutional compliance, and the wider implications of coercive economic practices for global order. Trade and sanctions operate within the same structure of asymmetrical interdependence, enabling states with central network positions to convert openness into coercive leverage. Geoeconomic power is increasingly exercised through the governance of connectivity rather than through economic exchange alone. The article contributes to the field by integrating debates on sanctions, trade, and interdependence into a more coherent account of how networked economic relations shape hierarchy and coercion in world politics.